Molluscan antimicrobial peptides, a review from activity-based evidences to computer-assisted sequences - H Li (Invertebrate Survival Journal, 2011)
Antimicrobial peptides (AMPs) represent the most universal immune effectors. Molluscs constitute the second largest animal phylum, after Arthropods, in term of number of species. Only a negligible number has been investigated regarding AMPs. The choice of the species to be studied relied on their economical importance and availability. First studies on molluscan AMPs dated from 1996 and were based on biological activities of biochemical-purified fractions. Such approach released all the original structures we know, with biological activity sometimes different from one isoform to another. Then, molecular biology techniques were applied to molluscan AMPs starting in 1999. Complete screening of genome expression in various situations became available, as well as some exotic Molluscs, the ones collected from deep-sea hydrothermal vent, for instance. Full sequences of active peptides and precursors, and gene organizations were established. A breakthrough consisted in the discovery of numerous AMP variants, even within the same animal. In addition, computer homology revealed the existence of already known AMPs in new studied molluscan species.